Association of Early β-Amyloid Accumulation and Neuroinflammation Measured With [11C]PBR28 in Elderly Individuals Without Dementia. (23rd March 2021) - Toppala, Sini; Ekblad, Laura L.; Tuisku, Jouni; Helin, Semi; Johansson, Jarkko J.; Laine, Hanna; Löyttyniemi, Eliisa; Marjamäki, Päivi; Blennow, Kaj; Zetterberg, Henrik; Jula, Antti; Viitanen, Matti; et al.
Abstract : Objective: To examine whether early β–amyloid (Aβ) accumulation and metabolic risk factors are associated with neuroinflammation in elderly individuals without dementia. Methods: We examined 54 volunteers (mean age 70.0 years, 56% women, 51% APOE [Latin Small Letter Open E]4 carriers) with the translocator protein (TSPO) tracer [ 11 C]PBR28 to assess neuroinflammation and with [ 11 C] Pittsburgh compound B (PiB) to assess cerebral Aβ accumulation. [ 11 C]PBR28 and [ 11 C]PiB standardized uptake value ratios (SUVRs) were quantified in 6 regions of interests by using the cerebellar cortex as a pseudo-reference and reference region, respectively. Fasting venous glucose, insulin, and high-sensitivity C-reactive protein (hs-CRP) values were determined. Homeostatic model assessment of insulin resistance (HOMA-IR) was calculated. A subset of individuals (n = 11) underwent CSF sampling, and Aβ40, Aβ42, total tau, phospho-tau, soluble TREM2, and YKL-40 levels were measured. Results: Among the whole study group, no significant association was found between [ 11 C]PiB and [ 11 C]PBR28 SUVR composite scores (slope 0.02, p = 0.30). However, higher [ 11 C]PiB binding was associated with higher [ 11 C]PBR28 binding among amyloid-negative ([ 11 C]PiB composite score ⩽1.5) (TSPO genotype–, age- and sex-adjusted slope 0.26, p = 0.008) but not among amyloid-positive (slope −0.004, p = 0.88) participants. Higher CSF soluble TREM2 ( r s = 0.72, p = 0.01) and YKL-40 ( r s = 0.63, p = 0.04) concentrations were associated with a higher [ 11 C]PBR28 composite score. Higher body mass index, HOMA-IR, and hs-CRP were associated with higher [ 11 C]PBR28 binding in brain regions where Aβ accumulation is first detected in Alzheimer disease. Conclusions: While there was no association between amyloid and neuroinflammation in the overall study group, neuroinflammation was associated with amyloid among the subgroup at early stages of amyloid pathology.